Satisfaction of women attended by the physiotherapy service during labor (Research, Society and Development, 2020)
Introduction: Pregnancy and childbirth are unique processes, which constitute a special experience in the universe of the pregnant woman and her partner, which involves families, professionals and the community, where an adequate intrapartum follow-up can improve women's satisfaction with that moment. Objective: to evaluate the level of satisfaction of puerperal women who were submitted to physical therapy in labor and delivery in public maternity hospitals in the city of João Pessoa. Methodology: cross-sectional study, carried out in the sector for the immediate postpartum period of two hospitals with maternity hospitals in the city of João Pessoa, in the period between August and November 2019, maternity hospitals have approximately 30 beds per accommodation puerperium and, therefore, the choice of 1 accommodation per maternity was adopted with the option of performing calculations based on the occurrence of events in 50% of the population, which guarantees the largest sample size. The sample consisted of fifteen women per maternity, drawn at random. Results and Discussion: The analysis of the data of the mothers who participated in the research shows that there was a prevalence of young women between 21 and 30 years old, the sample had multiparous women in the most diverse gestational ages, most of whom had vaginal delivery without anesthesia and did not have companion support during labor, most of which still have some laceration or cutting procedure. Conclusion: it is believed that this study contributes to a possible adaptation of the dynamics of service functioning, we show that the physiotherapist is the health professional who has all the knowledge to provide support to parturient women.